Perceived Instructional Supervision Practices, Professional Learning Communities Practices, And School Performance in The Division of Eastern Samar - Felicidad L. Duras (ELT Worldwide: Journal of English Language Teaching, 2022)
Instructional supervision is deemed effective way to support professional growth and competency and has been identified as an integral component of staff development while Professional Learning Communities (PLC) is believed to be a more effective way of continuing professional growth and development among its staff focused on the academic performance of learners. This study was based on determining the instructional supervision practices based on its four (4) dimensions, the professional learning communities practices based on five (5) dimensions and the school performance based on the quality parameter of School-Based Management (SBM) of the twenty-two (22) central schools of the Eastern Samar Division. Results revealed that the instructional supervision practices are perceived by the principals and the teachers to be “highly practiced.” Professional learning communities’ practices are likewise perceived by both respondents to be “very highly practiced.” Test on significant difference indicated that there is no significant difference in both the instructional supervision practices and professional learning communities’ practices as perceived by the elementary school principals and their respective teachers. Generally, none of the schools investigated have satisfied and surpassed the quality standards for school –based management as only more than one-half of the school population investigated fall under “moving towards mastery” level.